ANALYSIS OF RFID SYSTEMS IN LOGISTICS: ANALYSIS OF RFID SYSTEMS IN LOGISTICS - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The application of radio frequency identification is constantly expanding. The technology is sought in industries where control over the movement of objects, intelligent automation solutions, the ability to work in harsh working conditions, trouble-free operation, speed and reliability are required. By applying RFID, it is possible to track the movement of goods in real time, speed up the process of receiving and sending goods, increase the reliability and transparency of operations, and reduce the influence of the human factor.